Selection and characterization of Bacillus thuringiensis isolates with a high insecticidal activity against Spodoptera frugiperda (Lepidoptera: Noctuidae) - Cerqueira, Fernando Barnabe (2016)
Spodoptera frugiperda (SMITH, 1797) (Lepidoptera: Noctuidae) affects diverse crops of great economic interest, for instance, it can cause severe yield losses in maize, rice and sorghum. In this study, a selection and characterization of Bacillus thuringiensis (BERLINER, 1911) isolates with a high insecticidal activity against S. frugiperda was performed. Fifty-two crystal-forming B. thuringiensis isolates that were identified from 3384 Bacillus-like colonies were examined and screened by PCR for the presence cry genes (cry1, cry1Aa, cry1Ab, cry1Ac, cry1D, cry2 and cry2Ab). Four isolates that showed high toxicity towards S. frugiperda were shown to harbor cry2 genes. The crystals were analyzed by electron microscopy and showed bipyramidal and cuboidal shapes. Furthermore, these four isolates had lethal concentration (LC50) values of 44.5 ng/cm2 (SUFT01), 74.0 ng/cm2 (SUFT02), 89.0 ng/cm2 (SUFT03) and 108 ng/cm2 (SUFT 04) to neonate S. frugiperda larvae. An ultrastructural analysis of midgut cells from S. frugiperda incubated with the SUFT01 spore-crystal complex showed disruptions in cellular integrity and in the microvilli of the midgut columnar cells. The isolates characterized in this work are good candidates for the control of S. frugiperda, and could Â be used for the formulation of new bioinsecticides.